THE MASS SEED PRODUCTION OF GOLDEN TREVALLY FISH (Gnathanodon Speciosus Forsskal) WITH DIFFERENT FEED - Tony Setia Dharma (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2014)
ABSTRACT Golden trevally fish is a prospective commodity that can be cultured and contains high economic value. The purpose of this study was to determine the best type of food for golden trevally fish growth. The larval rearing were conducted using concrete tanks with 6 m3 of volume. Three different food were used as treatments, i.e: (a) pellet micro, (b) small shrimp, and (c) trash fish. The start of experiment for larvae were reared for 30 days old. The stocking density of larvae was reared at 10 pc/l. Sampling of larvae were conducted every 7 days to measure of survival rate (SR), total length (TL) and body weight (BW). The larvae were reared with flowthrow system. At 70 days old, larvae were harvested and graded. The results showed that there was no significantly different among treatments (P>0.05) for survival rate, but the growth was significantly difference among treatments (P<0.05). The survival rate (SR) treated with trash fish was 5.38±1.20%, small shrimp 4.05±1.10%, and micro pellet 4.01 ± 1.20%. The total length and weight treated with trash fish were 5.40 ± 0.80 cm and 53±0,50 mg, respectively, while treaded with small shrimp were 4.80 ± 0.20 cm and 61±0.30 mg, and micro pellet were 4.54±0.56 cm and 48±0.40 mg, respectively. Keywords: seed, food type, growth, survival, golden trevally fish.